THE EFFECT OF FAMILY SUPPORT ON THE STRESS LEVEL OF INMATES IN CLASS IIA CORRECTIONAL INSTITUTION YOGYAKARTA - Ariasmara, Sunu; Muhammad, Ali (Jurnal Kajian Pendidikan dan Psikologi, 2025)
The goal is to find out whether there is a Family Support on Stress Level in prisoners at the Yogyakarta Class IIA Correctional Institution. This research is a quantitative study using the correlational method. Data collection tools using questionnaires. The correlation value (R) is interpreted that the family support variable has a relationship in predicting the stress level variable. R square of 0.054 means that the effect of family support on stress level is 5%. So, it can be concluded that the higher the family support, the lower the stress level of prisoners at the Yogyakarta Class IIA Correctional Institution.